TELANG FLOWER KOMBUCHA SOLID BATH SOAP AS A HALAL AND ANTIMICROBIAL PHARMACEUTICAL BIOTECHNOLOGY PRODUCT - Rezaldi, Firman; Surya, Meylissa Servita; Maritha, Vevi; Ginanjar, Iin Hasan; Nurmaulawati, Rina (International Journal Mathla’ul Anwar of Halal Issues, 2024)
Excellent health is part of having immunity which tends to be stable, where normal flora is the most important parameter in increasing the body's resistance. Normal flora that is not well controlled can also increase the body's immune system to become threatened so that disease and infection have the potential to attack each individual. Smelly armpits are a sign of disease or Staphylococcus hominis infection. Women's intimate organs experiencing vaginal discharge is a sign of disease or infection caused by Candida albicans. The solution that can be offered to inhibit the growth of these two microbes is to bathe using herbal soap that is environmentally friendly and antimicrobial, namely solid bath soap made from the active ingredient of telang flower kombucha. This research aims to produce environmentally friendly pharmaceutical biotechnology products in the form of solid bath soap formulations and preparations made from the active ingredient of telang flower kombucha. This research is a laboratory experiment by making a solid bath soap base without active substances and a solid bath soap made from the active ingredient of butterfly pea flower kombucha with sugar concentrations including 20%, 30% and 40%. This research has proven that solid bath soap with the active ingredient telang flower kombucha at a concentration of 40% is significantly different as a pharmaceutical biotechnology product in inhibiting the growth of the two test microbes, both bacteria that cause underarm odor and pathogenic fungi that cause vaginal discharge in women's intimate organs at concentrations of 20% and 30%. based on one-way ANOVA analysis with a P value <0.05. This research can be proven and concluded that telang flower kombucha solid bath soap at a concentration of 40% is an effective treatment as a pharmaceutical biotechnology product and as an antimicrobial for both bacteria that cause underarm odor and pathogenic fungi that cause vaginal discharge in women's intimate organs